Ekonomi Sirkular Berbasis Syariah: Solusi untuk Pembangunan Berkelanjutan - Mashadi, Ali Imron (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2024)
This article explores the integration of circular economy and sharia principles as an innovative solution to achieve sustainable development. Through a systematic literature review, this study analyzes how Islamic values ??can strengthen the implementation of circular economy in achieving the Sustainable Development Goals (SDGs). The results show that sharia-based circular economy offers a holistic and ethical framework to address contemporary environmental and socio-economic challenges. The concept of maqasid sharia provides a strong moral foundation for sustainable economic practices, while Islamic financial instruments such as green sukuk and productive waqf can facilitate the transition to a circular economy. This integration not only supports environmental protection but also ensures social justice and inclusive economic welfare.